Recorridos Turísticos Rurales Comunitarios como Impulsadores de la Economía Regional. Caso Corregimiento El Caguán (Huila) (2022)
As is the case of different places that have an unexplored rural value, the Caguán corregimiento is presented as a place that has not been polished and valued with the due importance of not only local identity, but, of equal magnitude, the corregimiento contends for a higher scale value, called regional scale; From which traditional cultural and architectural characteristics are developed, which frame a component linked to the historical background that shaped what is now the capital of Huila, the city of Neiva. This is due to the fact that rural tourism in a generalized concept, due to social error, does not present the appropriate attention, mostly local and regional. Revealing promotion deficiency for those communities that are autonomous, but that have different characteristics to act as powers for the hierarchy of tourism and its branches. This being the case of the corregimiento el Caguán, for which it does not present direct relations primarily wit h its premises, without them understanding that they have an analogy of different cultural and architectural components that are waiting to be explored, extolling each one of its particularities and in turn protecting those components that make a place or space unique